In the name of god : preserving the sense of security in Malaysia - Yang Razali Kassim (2011)
The controversy over the Christian use of “Allah”, the divine name Muslims use for God, has taken a new twist as more provocations surfaced. The sense of insecurity in Malaysia can be eased through